2014
DOI: 10.2310/jim.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

A Cut-Point Value of Uncarboxylated to Carboxylated Index is Associated with Glycemic Status Markers in Type 2 Diabetes

Abstract: A value of ucOC/cOC index less than 0.3 is associated with markers of poor metabolic control in patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
9
1
1
Order By: Relevance
“…Similarly, to our results, Villafan-Bernal et al used the ucOC/OC index to predict the probability of having T2D in a cohort of T2D patients and healthy subjects. Patients with ucOC/OC index below 0.31 had 12.6-fold increased probability of developing T2D than patients with higher index 51 . These findings strengthen our above-mentioned results, suggesting that serum levels of ucOC could be a potential biomarker to estimate cardiovascular and T2D risk in MetS patients.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, to our results, Villafan-Bernal et al used the ucOC/OC index to predict the probability of having T2D in a cohort of T2D patients and healthy subjects. Patients with ucOC/OC index below 0.31 had 12.6-fold increased probability of developing T2D than patients with higher index 51 . These findings strengthen our above-mentioned results, suggesting that serum levels of ucOC could be a potential biomarker to estimate cardiovascular and T2D risk in MetS patients.…”
Section: Discussionmentioning
confidence: 89%
“…While cOC has high affinity for calcium ions contained in hydroxyapatite, is actively involved in osteogenesis[4] and enhances osteoclast maturation[5], ucOC functions as a regulatory hormone in glucose metabolism improving insulin sensitivity and secretion, β-cell mass and glucose tolerance[6,7]. Low serum OC levels and the index ucOC/cOC are associated with increased fasting plasma glucose (FPG) and IR in several cross-sectional and prospective studies[8-12] and with risk for developing type 2 diabetes (T2D)[10,13]. On the other hand, bone metabolism, T2D and cardiovascular diseases (CVD) interact with one another through complex mechanisms[14-21].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of OC in humans included both the carboxylated (cOC) and uncarboxylated forms (ucOC), whereas ucOC appeared associated to higher HOMA-B% levels, and thus to β-cell function, while cOC was associated to lower HOMA-IR values, more representative of insulin resistance [ 55 ]. Interestingly, some data suggested that values lower than a ucOC/cOC index cutoff, corresponding to 0.3, can be associated with markers of poor metabolic control in T2D [ 56 ].…”
Section: Vitamin D and Biomarkers Of Bone Turnovermentioning
confidence: 99%